2015
DOI: 10.1155/2015/961049
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Vitamin C as an Additive in Plasma of Stored Blood

Abstract: There is a dire necessity to improve blood storage and prolong shelf-life of blood. Very few studies have focused on oxidative stress (OS) in blood and its influence on plasma with storage. This study attempts to (i) elucidate the continuous changes occurring in plasma during storage through oxidant levels and antioxidant status and (ii) evaluate the influence of vitamin C (VC) as an additive during blood storage. Blood was drawn from male Wistar rats and stored for 25 days at 4°C. Blood samples were divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
1
9
1
Order By: Relevance
“…To test this possibility, clinical monitoring of hemolytic parameters could be considered in future or ongoing clinical trials. Moreover, our studies suggest that VC alone may have limited utility in blood storage, where it has been tested extensively (20,21). Rather, preservation of erythrocytes in solutions with glucose and alternative anti-oxidants might better prevent RBC oxidative stress and hemolysis and promote longer term erythrocyte stability during storage.…”
Section: Discussionmentioning
confidence: 98%
“…To test this possibility, clinical monitoring of hemolytic parameters could be considered in future or ongoing clinical trials. Moreover, our studies suggest that VC alone may have limited utility in blood storage, where it has been tested extensively (20,21). Rather, preservation of erythrocytes in solutions with glucose and alternative anti-oxidants might better prevent RBC oxidative stress and hemolysis and promote longer term erythrocyte stability during storage.…”
Section: Discussionmentioning
confidence: 98%
“…This observation, while preliminary, is suggestive of the fact that preserved energy homeostasis mitigates RBC spiculation, a “save or sacrifice” phenomenon to eliminate oxidation products (including oxidized lipids). However, preserved energy homeostasis in alkaline additives (especially PAG3M and E‐SOL 5) is not sufficient to completely prevent lipid oxidation, for which introduction of hydrophilic (e.g., ascorbate) or lipophilic (e.g., vitamin E) antioxidants may represent a better option . An alternative explanation to this phenomenon is an increase in oxidized lipid recycling through the Lands cycle, a phenomenon that is promoted by hypoxia 58 and may be similarly affected by alkalinization.…”
Section: Discussionmentioning
confidence: 99%
“…However, preserved energy homeostasis in alkaline additives (especially PAG3M and E-SOL 5) is not sufficient to completely prevent lipid oxidation, for which introduction of hydrophilic (e.g., ascorbate) or lipophilic (e.g., vitamin E) antioxidants may represent a better option. [30][31][32][33][34] An alternative explanation to this phenomenon is an increase in oxidized lipid recycling through the Lands cycle, a phenomenon that is promoted by hypoxia 58 and may be similarly affected by alkalinization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An antioxidant is defined as "any substance that, when present at low concentrations compared to those of an oxidizable substrate, significantly delays or prevents oxidation of that substrate" [11]. Various studies have reported the beneficial effects of antioxidants (L-carnitine [LC], curcumin [Cu], vitamin C [VC]) in blood storage solutions [12][13][14][15][16][17][18][19][20][21][22].…”
Section: L-carnitinementioning
confidence: 99%